OVERVIEW OF KNOWLEDGE AND COMPLIANCE IN ADOLESCENT WOMEN REGARDING THE CONSUMPTION OF BLOOD SUPPLEMENTING TABLETS - Handayani, Maulina; Khamadika, Ratih Latiffah (Ikatan Perawat Maternitas Indonesia Provinsi Jawa Barat, 2024)
Background : The prevalence of adolescents with anemia based on Riskesdas data in 2018 was 32%, where 3-4 out of 10 teenagers had anemia and the most age groups were 15-24 years old, this shows the importance of consuming iron tablet. Objectives : The purpose of this study is to determine the description of knowledge and compliance in female adolescent regarding the consumption of blood-added tablets at SMAN 6 Tangerang Selatan. Methods : The method used in this study is descriptive quantitative approach with survey method. The sample used were 90 female students of X and XI grade. The sampling technique used was proportion stratified random. Analysis of descriptive data by describing knowledge about iron deficiency anemia and adherence to consuming blood-added tablets in the frequency distribution tablets. Results : The results of this study indicate that out of 90 female students there are 69 respondents (76.7%) in Good knowledge category, 18 respondents (20%) in Sufficient category, 3 respondents (2%) in Poor category. Meanwhile. the level of compliance with non-compliance is 80 (88.9%) respondents and compliance is only 10 (11.1%) respondents. Conclusion of this research was majority respondents had good knowledge but non compliance regarding consumption of blood-added tablet. Future researchers are expected can explore factors influence the non compliance of consumption blood- added tablet and the importance of monitoring its consumption.